Organizational Pride Oriented the Commitment Behavior of the Service Provider (An Analytical Study of the Opinions of a Sample of Employees at Zain Iraq Wireless Telecommunications Company) - Khetam Dekhen Hamza (Scholars Digest Publishing, 2023)
The main purpose of the current study is to study the relationship between emotional organizational pride and attitude organizational pride and analyze the positive effects resulting from them, which are related to their role in guiding service provider behavior to commitment to customer service. The study population consisted of workers in the customer service department at Zain Iraq Wireless Communications Company. The data used in the main study were collected through a questionnaire form and distributed to a sample of (150) individuals working in the customer service department. Structural equation modeling was applied to test hypotheses based on a set of statistical methods. The study reached a set of results, the most important of which was the existence of a significant effect between organizational pride and the commitment of employees to serve customers.
Keywords: organizational pride, commitment to customer service, organizational commitment.